Coinhibitory Pathways in Immunotherapy for Cancer - Baumeister, Susanne H; Freeman, Gordon J; Dranoff, Glenn; Sharpe, Arlene H (Annual review of immunology, 2016)
The immune system is capable of recognizing tumors and eliminates many early malignant cells. However, tumors evolve to evade immune attack, and the tumor microenvironment is immunosuppressive. Immune responses are regulated by a number of immunological checkpoints that promote protective immunity and maintain tolerance. T cell coinhibitory pathways restrict the strength and duration of immune responses, thereby limiting immune-mediated tissue damage, controlling resolution of inflammation, and maintaining tolerance to prevent autoimmunity. Tumors exploit these coinhibitory pathways to evade immune eradication. Blockade of the PD-1 and CTLA-4 checkpoints is proving to be an effective and durable cancer immunotherapy in a subset of patients with a variety of tumor types, and additional combinations are further improving response rates. In this review we discuss the immunoregulatory functions of coinhibitory pathways and their translation to effective immunotherapies for cancer.